First trimester screening can predict adverse pregnancy outcomes. (1st June 2014) - Sharp, Andrew N.; Alfirevic, Zarko; Ghidini, Alessandro; Gratacos, Eduard
ABSTRACT There has been an increasing drive over the last two decades to push the detection of women at risk of adverse pregnancy outcomes into the first trimester. This has led to a plethora of techniques, risk assessments and biomarkers, both fascinating and bewildering in its breadth. Despite the vast amount of knowledge available, it is often difficult to determine what is practicable and valuable for clinical practice. This is especially true as earlier diagnosis does not necessarily equate to improved outcomes for mother and child. We suggest that, at least for preeclampsia, fetal growth restriction, spontaneous preterm birth and gestational diabetes, there are effective first trimester tests available to identify the women at risk of subsequently developing complications. Unfortunately, there are no currently reliable first trimester tests available for identifying women at risk of stillbirth. It is likely that this field will continue to develop over time, and we hope that new and better strategies will continue to emerge to target these clinically important pathologies. © 2014 John Wiley & Sons, Ltd.